Welfare issues in price control on occasions of calamities, emergencies, and like occurrences - Sonny N. Domingo; Ma. Divina C. Olaguera (Philippine Institute for Development Studies (PIDS), 2017)
Traditional interventions during and after major disaster events usually focus on the welfare of individuals and households, often at the expense or neglect of local economic recovery. The Price Act (Republic Act or RA 7581) establishes a mechanism that supposedly protects consumers from inadequate supply of goods and unreasonable price increase in occasions of disasters and emergencies. RA 7581 is an example of a double-edged policy which protects a section of the populace (consumers) and holds back another (local enterprises). This study focuses on the implications of RA 7581 during disaster events and answers issues on the effects of price control on consumer protection and local economic recovery as well as provides discourse on the effects of price control imposition during occasions of calamities, emergencies, and like occurrences.
Keywords: 330; Price control; DRRM; Price Act; Welfare Issues